Theory and Movement – From the Student Movement to Popular and Peasant Feminism: Encounters with Saffioti - Calaça, Michela (Pontifícia Universidade Católica de São Paulo, 2021)
This article takes as its point of departure the idea that life history is not something isolated from social relations in order to discuss the pertinence of Saffioti’s theoretical construction, both in the sense of contributing to the analysis of reality and to suggest organizational paths. Its objective is to discuss the relationships between political theory and action as an interweaving of social reality. Using the method known as life history, we try to show how the works of this author contribute to our understanding of the reality of the activist’s life. In addition, we present the debates we have witnessed in various spaces of action, which are about the social relations between class/gender/race/ethnicity, particularly in our Brazilian reality. For that purpose, the revival of the core of Saffiotti seems fundamental. Finally, in order to provoke reflection, we debate the relationship between political theory and action for transforming reality.